A Cross-National Study of Students' Understanding of Genetics Concepts: Implications from Similarities and Differences in England and Turkey. (6th April 2016) - Kılıç, Didem; Taber, Keith S.; Winterbottom, Mark
Abstract : This research is aimed at exploring 16- to 19-year-old students' understanding of fundamental genetics concepts, which has considerable importance for developing conceptual understanding of genetics related phenomena. A cross-national descriptive research method was used to explore English and Turkish students' understandings of genetics concepts. Data were collected by a two-tier multiple choice diagnostic instrument, The Two-Tier Genetics Concept Test, which required students to justify their choice of option by giving a reason. The results indicate that there are some differences between the English students' and Turkish students' understanding of fundamental concepts of genetics; however, there are some notable similarities between the alternative conceptions held by students in the two samples. The common alternative conceptions seen in both of the groups indicate that understanding the concepts occurred regardless of contextual factors. Nevertheless different proportions of the common alternative conceptions and different levels of understanding suggest that conceptualisations develop under the influence of different educational contexts.